Using Native American games to encourage physical activity in children - Litfin-Salt, Miriam (My University, 2015)
In response to public health reports pertaining to increasing rates of childhood obesity, the original intent of this project was to compare historical trends in toy purchases to current toy purchases. It was expected that choices would lean towards more sedentary games with present day purchases. The reasons for following a different line of study will be explained in detail at a later point. The internship portion of the project involved coordinating with the Northview Elementary School’s summer school session. Their summer school curriculum focused on Native American culture. I collected information pertaining to traditional Native American games, then gathered natural and recycled material to make usable reproductions of some Native American toys. First I gave a small presentation to the whole group about how each style of toy was used and then the box of toys was made available to the children at recess. They could choose what toys they wanted to play with at will. I made arrangements to accompany them to recess twice a week.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: Litfin-Salt, M. (2004). Using Native American games to encourage physical activity in children. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Indians of North America--Games; Physical fitness for children; Exercise for children; Reports; Reports